Epidemiology and risk factors for contralateral proximal femur fracture: a single center retrospective cohort study on 1022 patients - Murena , Luigi; Ratti, Chiara; Maritan, Guido; Rasio, Nicholas; Pistorio , Sabrina; Cusitore, Marcello; Canton , Gianluca (Acta Biomedica Atenei Parmensis, 2020)
Summary. Background and aim of the work: Given the high impact of proximal femur fractures (PFFs) on elderly patients and healthcare systems, the burden of contralateral PFFs might be overlooked. Aim of the study is to analyze the epidemiology and risk factors of contralateral proximal femur fractures. Secondary aim is to detect mortality rate differences in first and contralateral PPF. Methods: A population of 1022 patients admitted for proximal femur fractures in a single center was studied. Prevalence at admission as well as incidence of contralateral PFF during a 18 to 36 months follow-up was recorded. Epidemiology of contralateral PFF was studied recording number of events, time to second fracture and fracture type. Mortality at 1-year was recorded for all patients and compared between first and second PFF patients. Comorbidities, pharmacotherapy, BMI, MNA and SPMSQ were studied as possible risk factors. Results: Prevalence and incidence of contralateral PFFs were 9.4% and 6.5% respectively. Median time to second fracture was 12 months. One-year mortality of contralateral PFFs was significantly lower (20.5% vs 25.1%, p 0.003) than first PFF. Contralateral fracture patients had a significantly lower BMI and a significantly lower proportion of malnourished patients. Conclusions: The incidence and prevalence of contralateral PFFs is relevant. Mortality of contralateral PFFs results to be lower than first PFF. Patients with higher BMI and malnourished patients have a lower risk of contralateral PFF.